Modal Sosial Masyarakat Jalawastu Dalam Membangun Integrasi Sosial Dengan Pemerintah Daerah - Subiyanto Subiyanto; Wahyu Jati Kusuma; R Samidi; Enkin Asrawijaya (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2022)
The purpose of this study is to find out how the social capital built by the Jalawastu community is able to build consensus with the local government. Harmony through integration is the key word developed by the people of Jalawastu with the world outside their community, especially with the local government. This research method will use James P. Spradley's